Twitter titling Corpus - Berg, Esther van den (Universität, 2019)
The Twitter Titling Corpus contains 4002 stance-annotated tweets collected between 20 June 2017 and 30 August 2017 mentioning 6 presidents. Each tweet is annotated for the naming form used to refer to the president, for the purpose of a study on the relation between naming variation and stance (cited below). This data is to be used for research purposes only.
Gesehen am 02.09.2019
Keywords: Forschungsdaten; Datenbank